2012
DOI: 10.3390/rs4010180
|View full text |Cite
|
Sign up to set email alerts
|

Use of Variogram Parameters in Analysis of Hyperspectral Imaging Data Acquired from Dual-Stressed Crop Leaves

Abstract: Abstract:A detailed introduction to variogram analysis of reflectance data is provided, and variogram parameters (nugget, sill, and range values) were examined as possible indicators of abiotic (irrigation regime) and biotic (spider mite infestation) stressors. Reflectance data was acquired from 2 maize hybrids (Zea mays L.) at multiple time points in 2 data sets (229 hyperspectral images), and data from 160 individual spectral bands in the spectrum from 405 to 907 nm were analyzed. Based on 480 analyses of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…The research objective is therefore to identify portions of the wavelength spectrum, in which seeds show a significant and measurable change in certain parts of the examined reflectance spectrum and associated that change in reflectance with certain traits, such as, germination (yes/no). A wide range of classification methods have been used as part of using reflectance data to characterize seeds and food products; these classification methods include support vector machine (SVM) [32], variogram analysis [33,34], partial least square analysis [35], and linear discriminant analysis (LDA) [36]. LDA is based on discriminant functions, which are linear combinations of features (in this case reflectance values in spectral bands) and with one function for each target class.…”
Section: Introductionmentioning
confidence: 99%
“…The research objective is therefore to identify portions of the wavelength spectrum, in which seeds show a significant and measurable change in certain parts of the examined reflectance spectrum and associated that change in reflectance with certain traits, such as, germination (yes/no). A wide range of classification methods have been used as part of using reflectance data to characterize seeds and food products; these classification methods include support vector machine (SVM) [32], variogram analysis [33,34], partial least square analysis [35], and linear discriminant analysis (LDA) [36]. LDA is based on discriminant functions, which are linear combinations of features (in this case reflectance values in spectral bands) and with one function for each target class.…”
Section: Introductionmentioning
confidence: 99%
“…In which a, b, and c are fitted coefficients and D denotes the lag distance and F(D) is the semi-variance at lag distance, D. Although other regression fits are typically used (Nansen, 2012), an important advantage of the regression fit in Eq. (2) is a very high level of regression convergence.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…Spatial structure analysis based on geostatistics (variogram analysis) is considered one of the most powerful and robust approaches to spatial data analysis (Isaaks and Srivastava, 1989), and recent studies have shown how variogram parameters derived from high-resolution reflectance data can be used to detect different traits in a range of target objects (Nansen, 2011(Nansen, , 2012Nansen et al, 2010a;Nansen et al, 2010b;Nansen et al, 2009;Nansen et al, 2010c). In the variogram analysis (PROC VARIOGRAM) of reflectance data at 782 nm, we used the following variogram settings: (1) lag distances = 1, and (2) number of lag intervals = 10.…”
Section: Data Processing and Analysismentioning
confidence: 99%
See 2 more Smart Citations